Crisis Situations Among Children/Adolescents with Emotional and Behavioural Disorders in Education - Vrhunc Pfeifer, Katja (Revija za elementarno izobraževanje, 2021)
Employees in education, especially in residential treatment centres, face crisis situations as a result of emotional and behavioural problems/disorders of children and adolescents. They most often face various types of violence, self-aggression, use of illicit substances and abuse. Cases of children and adolescents with mental health problems are frequent. Crisis interventions differ with the complexity of the situation, and regardless of the approach, an appropriate relationship is crucial to any solution. The purpose of this article is to present and elaborate the most common crisis situations and some successful interventions in such cases.
Keywords: crisis situation; emotional and behaviouural disorders; residential treatment centre; crisis intervention; professionals